Underwater sound data, recorded during a 18-month in situ experiment in Helgoland, Germany - Alexandre Le Moal; Laura Payton; Yannick Geerebaert; Bettina Meyer; Bernadette Pogoda; Damien Tran (PANGAEA, 2025)
This dataset shows the hourly sound pressure magnitude data measured underwater throughout the 18 months of experiment (11th of May 2023 – 31st of August 2024) in Helgoland (Margate) for different frequencies (10 Hz, 20 Hz, 30 Hz, 40 Hz, 50 Hz, 60 Hz, 70 Hz, 80 Hz, 90 Hz, 100 Hz, 200 Hz, 300Hz, 400 Hz, 500 Hz, 600 Hz, and 700 Hz) recorded by the HFNI valvometer. The mean sound pressure magnitude is also presented. Missing data corresponds to the stop of recording of the valvometer.
In: Le Moal, A et al. (2025): Valve behavior of the European flat oyster Ostrea edulis and associated underwater sound and temperature data, recorded during a 18-month in situ experiment in Helgoland, Germany [dataset bundled publication]. PANGAEA, https://doi.org/10.1594/PANGAEA.983652